2020
DOI: 10.21203/rs.3.rs-25530/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long noncoding RNA RP11-757G1.5 sponges miR-139-5p and upregulates YAP1 thereby promoting the proliferation and liver, spleen metastasis of colorectal cancer

Abstract: Background: Accumulating evidence indicates that long non-coding RNAs (lncRNAs) acting as crucial regulators in tumorigenesis. However, its biological functions of lncRNAs in colorectal cancer (CRC) have not been systematically clarified. Methods: An unbiased screening was performed to identify disregulated lncRNAs revealed to be implicated in CRC carcinogenesis according to an online-available data dataset. In situ hybridization (ISH), RT-qPCR and RNA fluorescence in situ hybridization (RNA-FISH) were applied… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In addition, lncRNAs also act as competing endogenous RNA (ceRNA), interacting with miRNAs, and by affecting the expression of messenger RNA (mRNA) ( Li S. et al, 2020 ). Zhu et al (2020) found a new type of oncogenic lncRNA RP11-757G1.5 through microarray analysis, which is overexpressed in CRC tissues, especially in aggressive cases. In addition, the upregulation of RP11-757G1.5 is closely related to the adverse clinical outcome of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, lncRNAs also act as competing endogenous RNA (ceRNA), interacting with miRNAs, and by affecting the expression of messenger RNA (mRNA) ( Li S. et al, 2020 ). Zhu et al (2020) found a new type of oncogenic lncRNA RP11-757G1.5 through microarray analysis, which is overexpressed in CRC tissues, especially in aggressive cases. In addition, the upregulation of RP11-757G1.5 is closely related to the adverse clinical outcome of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Further functional analysis showed that RP11-757G1.5 can promote cell proliferation in vitro and in vivo . The mechanism for this phenomenon is that RP11-757G1.5 regulates the expression of YAP1 and promotes the development of CRC by competitively binding miR-139-5p to inhibit its activity ( Zhu et al, 2020 ). In this study, we combined the previous research results to screen and verify the high expression of lncRNA KCNQ1OT1.…”
Section: Discussionmentioning
confidence: 99%
“…Salmena et al proposed the competitive endogenous RNA (ceRNA) hypothesis, which suggests that mRNAs, lncRNAs, and other non-coding RNAs can be used as natural miRNA "sponges" that participate in the process of RNA degradation and post-translational modification together with ordinary miRNA response elements (MREs) (8). Previous studies have confirmed that non-coding RNAs are involved in tumorigenesis, invasion, metastasis, and other biological processes involved in colon cancer (9). We need more research to discover whether MIRNA plays an important role in the formation of MSI-H CRC.…”
Section: Introductionmentioning
confidence: 99%